Thirty-day mortality in patients undergoing laparotomy for small bowel obstruction. Issue 8 (30th March 2018) - Peacock, O; Bassett, M G; Kuryba, A; Walker, K; Davies, E; Anderson, I; Vohra, R S
Abstract: Background: Small bowel obstruction (SBO) is a common indication for emergency laparotomy. There are currently variations in the timing of surgery for patients with SBO and limited evidence on whether delayed surgery affects outcomes. The aim of this study was to evaluate the impact of time to operation on 30-day mortality in patients requiring emergency laparotomy for SBO. Methods: Data were collected from the National Emergency Laparotomy Audit (NELA) on all patients aged 18 years or older who underwent emergency laparotomy for all forms of SBO between December 2013 and November 2015. The primary outcome measure was 30-day mortality, with date of death obtained from the Office for National Statistics. Patients were grouped according to the time from admission to surgery (less than 24 h, 24–72 h and more than 72 h). A multilevel logistic regression model was used to explore the impact of patient factors, primarily delay to surgery, on 30-day mortality. Results: Some 9991 patients underwent emergency laparotomy requiring adhesiolysis or small bowel resection for SBO. The overall mortality rate was 7·2 per cent (722 patients). Within each time group, 30-day mortality rates were significantly worse with increasing age, ASA grade, Portsmouth POSSUM score and level of contamination. Patients undergoing emergency laparotomy more than 72 h after admission had a significantly higher risk-adjusted 30-day mortality rate (odds ratio 1·39, 95 per cent c.i. 1·09 to 1·76). Conclusion: In patients who require an emergency laparotomy with adhesiolysis or resection for SBO, a delay to surgery of more than 72 h is associated with a higher 30-day postoperative mortality rate. Abstract : Avoid unnecessary delay